EFFECT OF REPLACEMENT OF FISH MEAL BY GOLDEN SNAIL MEAL AT DIFFERENT LEVEL IN THE DIET ON THE PERFORMANCE AND CARCASS OF MUSCOVY DUCKS - I W., TAMI,; MASTIKA, I M.; NURIYASA, I M. (Majalah Ilmiah Peternakan, 2017)
An experiment was conducted on the replacement of fish meal with golden snails meal at different level onperformance and carcass of muscovy ducks. A randomized complete block design (RCBD), with five treatmentsand four replications was used in this study so in other words there were 20 experiments unit conducted. Muscovyducks were given diet using 15% fish meal as a control diet (R0), the replacement of 25% fish meal with golden snailsmeal (R1), the replacement of 50% fish meal with golden snails meal (R2), replacement 75% fish meal with goldensnails meal (R3) and 100% replacement of fish meal with golden snails meal (R4). Meal Rations and drinking waterare provided adlibitum. The results of the experiment showed that there was no significant difference (P>0.05)among in five treatments on the performances and carcass of muscovy ducks. The results also showed Muscovyduck given diet 75% replacement of fish meal with golden snails meal (R3) produced the highest performance andcarcass. Based on the results of this experiment it was concluded that the replacement of fish meal with goldensnails meal up to 100% did not affect performance and carcass of muscovy ducks.